Exometabolomic exploration of culturable airborne microorganisms from an urban atmosphere - R. Jin; W. Hu; W. Hu; P. Duan; M. Sheng; D. Liu; Z. Huang; M. Niu; L. Wu; J. Deng; P. Fu; P. Fu (Atmospheric Chemistry and Physics)
The interactions of metabolically active atmospheric microorganisms with cloud organic matter can alter the atmospheric carbon cycle. Upon deposition, atmospheric microorganisms can influence microbial communities in surface Earth systems. However, the metabolic activities of cultivable atmospheric microorganisms in settled habitats remain less understood. Here, we cultured typical bacterial and fungal species isolated from the urban atmosphere using tryptic soy broth (TSB) and Sabouraud dextrose broth (SDB), respectively, and investigated their exometabolites to elucidate their potential roles in biogeochemical cycles. Molecular compositions of exometabolites were analyzed using ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry. Annotation through the Kyoto Encyclopedia of Genes and Genomes database helped identify metabolic processes. Results showed that bacterial and fungal strains produced exometabolites with lower H /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1b4178c77ca0d4bfee6c9ddd864f3a43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1805-2025-ie00001.svg" width="8pt" height="14pt" src="acp-25-1805-2025-ie00001.png"/></svg:svg> C and higher O /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="527256ea34e0af356380afd605ccefc0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1805-2025-ie00002.svg" width="8pt" height="14pt" src="acp-25-1805-2025-ie00002.png"/></svg:svg> C ratios compared with both consumed and resistant compounds. As CHON compounds are abundant in both TSB (85 %) and SDB (78 %), CHON compounds also constituted over 50 % of the identified exometabolite formulas. Bacterial strains produced more abundant CHONS compounds (25.2 %), while fungal exometabolites were rich in CHO compounds (31.7 %). These microbial exometabolites predominantly comprised aliphatic/peptide-like and carboxyl-rich alicyclic molecule (CRAM)-like compounds. Significant variations in metabolites were observed among different microbial strains. Bacteria exhibited proficiency in amino acid synthesis, while fungi were actively involved in amino acid metabolism, transcription, and expression processes. Lipid metabolism, amino acid metabolism, and carbohydrate metabolism varied widely among bacterial strains, while fungi exhibited notable differences in carbohydrate metabolism and secondary metabolism. This study provides new insights into the transformation and potential oxidative capacity of atmospheric microorganisms concerning organic matter at air–land/water interfaces. These findings are pivotal for assessing the biogeochemical impacts of atmospheric microorganisms in clouds or following their deposition.